Analysis Of The Meaning Of Plurality, Pluralism, And Tolerance Based On The Interpretation Of The Quran QS. Al-Kafirn - Ridwan, Rizki Muhamad; Rahmat, Munawar; Parhan, Muhamad (Al-Ulum: Jurnal Pendidikan Islam, 2024)
Abstract: Various views on forms of tolerance in responding to diversity and differences, including race, culture, ethnicity, religion and language in Indonesia, are both facts and problems of social phenomena that emerge in modern life and influence the lives of religious communities. Tolerance is an attitude to make social life peaceful, harmonious and harmonious despite these differences. The aim of this research is to explore more deeply the three meanings of the concept of tolerance, namely pluralism, plurality and tolerance based on Al-Kafirun's letter. The results of this research found that plurality is the fact and reality of existing differences, pluralism is an attitude of seeing differences with equality - however, the concept of Islamic pluralism does not extend to religious pluralism because this is considered to exceed the limits and essence of the meaning of tolerance itself, and tolerance. in reviewing the interpretation of Al-Kafirun's letter in several books and figures, namely the attitude of appreciating, respecting, believing in religion without justifying or mixing up religious teachings. This research uses a literature study method by examining the writings of figures, the works of book and journal writers and the interpretation of Surah Al-Kafirun in tafsir books by several figures. It is hoped that this research can provide deeper insight, knowledge, attitudes and points of view regarding the meaning and nature of tolerance and provide a correct understanding of the attitudes that must be prioritized in responding to differences.